Sequential autologous CAR-T and allogeneic CAR-T therapy successfully treats central nervous system involvement relapsed/refractory ALL: a case report and literature review - Liu, Yifan; Li, Yanfen; Yu, Zhangyu; Wang, Rongrong; Jing, Yu (Frontiers in Oncology, 2024)
Background: The central nervous system (CNS) is the most common site of extramedullary invasion in acute lymphoblastic leukemia (ALL), and involvement of the CNS is often associated with relapse, refractory disease, and poor prognosis. Chimeric antigen receptor-T (CAR-T) cell therapy, a promising modality in cancer immunotherapy, has demonstrated significant advantages in the treatment of hematological malignancies. However, due to associated adverse reactions such as nervous system toxicity, the safety and efficacy of CAR-T cell therapy in treating CNSL remains controversial, with limited reports available. Case report: Here, we present the case of a patient with confirmed B-ALL who experienced relapse in both bone marrow (BM) and cerebrospinal fluid (CSF) despite multiple cycles of chemotherapy and intrathecal injections. The infusion of autologous CD19 CAR-T cells resulted in complete remission (CR) in both BM and CSF for 40 days. However, the patient later experienced a relapse in the bone marrow. Subsequently, allogeneic CD19 CAR-T cells derived from her brother were infused, leading to another achievement of CR in BM. Significantly, only grade 1 cytokine release syndrome (CRS) and immune effector cell-associated neurotoxicity syndrome (ICANS) events were detected during the treatment period and showed improvement with symptomatic management. During subsequent follow-up, the patient achieved a disease-free survival of 5 months and was successfully bridged to hematopoietic stem cell transplantation. Conclusion: Our study provides support for the argument that CNS involvement should not be deemed an absolute contraindication to CAR-T cell therapy. With the implementation of suitable management and treatment strategies, CAR-T therapy can proficiently target tumor cells within the CNS. This treatment option may be particularly beneficial for relapsed or refractory patients, as well as those with central nervous system involvement who have shown limited response to conventional therapies. Additionally, CAR-T cell therapy may serve as a valuable bridge to allogeneic hematopoietic stem cell transplantation (allo-HSCT) in these patients.